(3ZQQ GdMce hOQS Gdcdes - (3YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdGeOi GdJejeis; (3YHO GdhGMO Hf eMeO Hf YHO GdhGMO GdJejej GdGeOj, CHh GdaJM , fGUM GdOjf,J (B550 (3g` s ((3GdeOjfI GdefhQI s)
(3ChdgG (B:s
(3GdMeO ddg GdPi gOGfG HJhajbg Edi LGOI WQjbg hHYO aEf GdPi MOGfi Ydi JNUjU ahGjO gPG GdcJGH hJYdjbgG hLeY cdeI hJfejbgG s
(3BNQgG (B:s
(3jYLHfi ef GdQLd Cf jQi Ybdg RGjOkG Ydi dSGfg hdGjQi dSGfg RGjOkG Ydi Ybdg JeJ HMeO Gddg s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3JHUQI GdYfhGf (B:s
(3oefJNHs
Keywords: (3GdeYGQa GdYGeIs